2013
DOI: 10.1039/c2cc33706a
|View full text |Cite
|
Sign up to set email alerts
|

Copper-catalyzed direct oxidative annulation of N-iminopyridinium ylides with terminal alkynes using O2as oxidant

Abstract: The aerobic direct dehydrogenative annulation of N-iminopyridinium ylides with terminal alkynes leading to pyrazolo[1,5-a]pyridine derivatives has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(29 citation statements)
references
References 72 publications
0
29
0
Order By: Relevance
“…The mechanistic studies suggested that a Cu(I)/Cu(III) catalytic cycle was involved, where Cu(I) was oxidized by O 2 to form the Cu(III) exocyclic species 32 . During the process, silver carbonate would serve as a cocatalyst to promote the formation of intermediate alkynyl copper(I) species 35 (Scheme ) 19…”
Section: Ch Functionalization Of N‐imide Ylidesmentioning
confidence: 99%
“…The mechanistic studies suggested that a Cu(I)/Cu(III) catalytic cycle was involved, where Cu(I) was oxidized by O 2 to form the Cu(III) exocyclic species 32 . During the process, silver carbonate would serve as a cocatalyst to promote the formation of intermediate alkynyl copper(I) species 35 (Scheme ) 19…”
Section: Ch Functionalization Of N‐imide Ylidesmentioning
confidence: 99%
“…Of particular relevance is the propensity of these aminides to undergo intermolecular [3+ +2] dipolarc ycloadditions with electron-deficient alkynes [28] or terminal alkynes in the presence of silver salts andp alladium [29] or copper [30] catalysts to yield pyrazolo[1,5-a]pyridines,o rp yrido[1,2-a]indazolesf rom benzyne precursors. [31] Stereoselective [3+ +3]-couplings with vinylogous rhodium carbenes, [32] or between cyclopropanesa nd (iso)quinolinium-N-aminides [33] are also known.O ther transformationsi nclude stereoselective reductions, [34] directed C À Hf unctionalisations, [35] intramolecular cyclisations with tethered enolates or thiocyanates, [36] as well as photochemicale limination of pyridine to form electrophilic acyl nitrenes, or ringexpansion to diazepines.…”
mentioning
confidence: 99%
“…Through oxidative Cu-catalysis, we developed an aerobic oxidative dehydrogenative annulation of N-iminopyridinium ylides with terminal alkynes via C-H bond direct alkynylation leading to pyrazolo[1,5-a]pyridine derivatives (Scheme 1a). [6] zation. Intermediate B undergoes reductive elimination to afford the direct alkynylation intermediate C, in which the alkyne can be activated by copper catalyst.…”
Section: Methodologies Through C-h Bond Cleavagementioning
confidence: 99%